Analysis of dehydration and strength in elite badminton players - Abian-Vicen, J.; Del Coso, J.; Gonzalez-Millan, C.; Salinero, J. J.; Abian, P. (PLOS ONE, 2012)
The negative effects of dehydration on aerobic activities are well established. However, it is unknown how dehydration affects intermittent sports performance. The purpose of this study was to identify the level of dehydration in elite badminton players and its relation to muscle strength and power production.